2005
DOI: 10.1044/0161-1461(2005/025)
|View full text |Cite
|
Sign up to set email alerts
|

Intervention With Linguistically Diverse Preschool Children

Abstract: SLPs should provide services to linguistically diverse preschool-age children with LI in a manner that effectively supports the development of the home language. Parent and paraprofessional training along with peer-mediated models of intervention are presented as two possible methods for facilitating the home language in children with LI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(86 citation statements)
references
References 52 publications
7
76
1
2
Order By: Relevance
“…Children who demonstrated language maintenance were able to demonstrate more vocabulary and language skills than the children in the language loss group. Our results are consistent with a body of emerging research that has asserted that preservation of home language and culture ensures optimal continued language development for young emergent bilinguals (Genesee et al, 2004;Guiberson, 2005;Gutierrez-Clellen, 1999;Kay-Raining Bird et al, 2005;Kohnert, Yim, Nett, Kan, & Duran, 2005;Moore & Perez-Mendez, 2006;Restrepo & Kruth, 2000). Our analyses also suggest that (a) language loss can occur under various language usage and exposure conditions and (b) a number of differing language behaviors may be observed.…”
Section: Discussionsupporting
confidence: 93%
“…Children who demonstrated language maintenance were able to demonstrate more vocabulary and language skills than the children in the language loss group. Our results are consistent with a body of emerging research that has asserted that preservation of home language and culture ensures optimal continued language development for young emergent bilinguals (Genesee et al, 2004;Guiberson, 2005;Gutierrez-Clellen, 1999;Kay-Raining Bird et al, 2005;Kohnert, Yim, Nett, Kan, & Duran, 2005;Moore & Perez-Mendez, 2006;Restrepo & Kruth, 2000). Our analyses also suggest that (a) language loss can occur under various language usage and exposure conditions and (b) a number of differing language behaviors may be observed.…”
Section: Discussionsupporting
confidence: 93%
“…More specifically, if the exposure to either the host or the ethnic language falls below a certain limit, a bilingual child will not acquire full competence in that particular language (Genesee 2008). If a child does not develop the ethnic language well, this can have long-term effects on the social, emotional and academic development and family dynamics (Kohnert et al 2005). However, it can be expected that the thirdgeneration toddlers in this study will eventually use the Dutch language more than their second-generation mothers (Hakuta and D'Andrea 1992).…”
Section: Discussionmentioning
confidence: 95%
“…The host language is important for children in their school environment and daily life in the host country, whereas the maintenance of the ethnic language can be important in the home environment and is part of the children's cultural background. Studies in other countries and with other ethnic groups have shown that mothers' increase of the host language use with their children might be at the expense of developing ethnic language skills but without any significant benefit for the children's host language development (Hammer et al 2009;Kohnert et al 2005). If the same is true for Turkish mothers in The Netherlands, informing these mothers about such processes is desirable.…”
Section: % Non-western Immigrants In Neighborhoodmentioning
confidence: 89%
“…Bilingual children with language disorders may be at an even greater risk for L1 loss, because they encounter the same social factors as their bilingual peers with typical development and struggle with additional difficulties in language learning Restrepo & Kruth, 2000). Treatment planning for this population needs to include systematic support of the first language in order to increase communication between parents and children and promote children's overall well-being (Kohnert, Yim, Nett, Kan, & Duran, 2005).…”
Section: Bilingual Pli Profilementioning
confidence: 99%